Developing The English Version of The Diocese of Malang Website - Maria Talitakumi Widiastuti (UPT P2M Politeknik Negeri Malang, 2021)
In order to attract the foreign visitors of churches in Malang, the development of English version of the Diocese of Malang is created. To develop it, the researcher used the modified Design and Development Research steps by Borg and Gall. The steps are Research and Information Collection, Product Development, Expert Validation, Revision and Evaluation, Try Out the Product/Field Testing, Revision and Evaluation, and Final Product. The product is resulted to be Diocese of Malang website, complete with its English version. The English version result had been validated, and had been assessed by an expert and several respondents in the validation process and field testing. Both of the assessments process showed that the product could be used. The suggestions from the expert validation and field testing also had been received for the revision. The researcher suggested the Diocese of Malang to provide some pictures in the articles so that it would not look boring. The researcher also suggested for future researcher to take part in translating the remaining contents of Diocese of Malang since the researcher could not translate all the contents in the website due to time limit.